EULERIAN AND HAMILTONIAN PROPERTIES OF GALLAI AND ANTI-GALLAI TOTAL GRAPHS - Garg, Pravin; Sinha, Deepa; Goyal, Shanu (Journal of the Indonesian Mathematical Society, 2015)
Let $G = (V, E)$ be a graph. The Gallai total graph $Γ_T(G)$ of $G$ is the graph, where $V(Γ_T(G))=V \cup E$ and $uv \in E(Γ_T(G))$ if and only if \begin{itemize} \item[$(i)$] $u$ and $v$ are adjacent vertices in $G$, or \item[$(ii)$] $u$ is incident to $v$ or $v$ is incident to $u$ in $G$, or \item[$(iii)$] $u$ and $v$ are adjacent edges in $G$ which do not span a triangle in $G$. \end{itemize} The anti-Gallai total graph $Δ_T(G)$ of $G$ is the graph, where $V(Δ_T(G))=V \cup E$ and $uv \in E(Δ_T(G))$ if and only if \begin{itemize} \item[$(i)$] $u$ and $v$ are adjacent vertices in $G$, or \item[$(ii)$] $u$ is incident to $v$ or $v$ is incident to $u$ in $G$, or \item[$(iii)$] $u$ and $v$ are adjacent edges in $G$ and lie on a same triangle in $G$. \end{itemize} In this paper, we discuss Eulerian and Hamiltonian properties of Gallai and anti-Gallai total graphs.DOI : http://dx.doi.org/10.22342/jims.21.2.230.105-116